An Analysis of the Main Character’s Conflict in the Movie The Protégé - Agustinus Dappa Loka, Agus; Ni Nyoman Deni Ariyaningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Literature indicates the appreciation of writing as fine art. Additionally, it alludes to the competition that presents arguments, analyzes, dramatizes, and communicates circumstances and feeling through stories. One example of literary work is a movie. The aim of this study was to find out the main character’s conflict in the movie the Protégé by analyzing the dialogues and scenes shown in the film. A qualitative method was used in this research. This study was focusing on describing the internal and external conflict. The data were collected by watching the film, understanding the substance, and correlating it to the subject. The result of this shows that the main character faced two types of conflict; external and internal conflict. The kind of external conflict faced by the main character is Man-against-Man which is Anna between Don Preda and Monsieur. The conflict ends in murder. The Internal conflict faced by the main character is sadness when she found out that Moody was passed away, someone who has been taking care of her since she was a child.